Reactive Oxygen Species as Potential Drivers of the Seed Aging Process - Kurek, Katarzyna (Plants (Basel), 2019)
Seeds are an important life cycle stage because they guarantee plant survival in unfavorable environmental conditions and the transfer of genetic information from parents to offspring. However, similar to every organ, seeds undergo aging processes that limit their viability and ultimately cause the loss of their basic property, i.e., the ability to germinate. Seed aging is a vital economic and scientific issue that is related to seed resistance to an array of factors, both internal (genetic, structural, and physiological) and external (mainly storage conditions: temperature and humidity). Reactive oxygen species (ROS) are believed to initiate seed aging via the degradation of cell membrane phospholipids and the structural and functional deterioration of proteins and genetic material. Researchers investigating seed aging claim that the effective protection of genetic resources requires an understanding of the reasons for senescence of seeds with variable sensitivity to drying and long-term storage. Genomic integrity considerably affects seed viability and vigor. The deterioration of nucleic acids inhibits transcription and translation and exacerbates reductions in the activity of antioxidant system enzymes. All of these factors significantly limit seed viability.